Diurnal distribution of fish abundance and size composition in the Danjiangkou Reservoir, China - Arunjith, T. S.; Cheng, Fei; Wang, Zhen; Divya, K. R.; Xie, Songguang (Indian Journal of Fisheries, 2022)
Abundance and distribution information of fish in reservoirs is fundamental for efficient fishery management and conservation. However, habitat characteristics of large reservoirs usually make the traditional survey techniques impractical in acquiring these information. In this study, we investigated diurnal and vertical distribution of fish abundance and size composition in the middle section of the Danjiangkou Reservoir through hydroacoustic survey. Fish abundance estimated at night was 4.97 times of that during day. Fishes were highly concentrated in the water-depth layers between 10 and 20 m at night and scattered evenly across whole water column during day. Fish was highly dominant by individuals smaller than 5.5 cm total length (TL) at night and by individuals between 6.2 and 7.8 cm TL during day. Size composition was constant across depth between 10 and 25 m at night and between 15 and 25 m during day, while the proportion of small-sized fish was higher than in the other water-depth layers. Our results indicated an intensive diurnal movement of fish in the reservoir which provides basic information for efficient fishery management on juvenile fish in the littoral zone during day and the diurnal movement pattern in the reservoir suggests that hydroacoustic surveys should be conducted at night for accurate abundance estimation in large reservoirs.Keywords: Depth preferences, Diurnal distribution, Hydroacoustic survey, Reservoir, Size composition